Skiing Trauma and Safety: Seventh International Symposium 1989
DOI: 10.1520/stp19475s
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Forces on the Anterior Cruciate Knee Ligament During Backward Falls While Skiing

Abstract: In recent years a dramatic increase has been observed in isolated anterior cruciate knee ligament (ACL) lesions and in knee sprains where the principle injury has been to the ACL. Traditional mechanisms for this type of injury are not, in general, consistent with the type of fall nor do they explain why there should be such an increase in ACL injuries. One new mechanism that has been proposed is the boot-induced anterior drawer. In a fall involving this mechanism, a skier is off-balance posteriorly such that l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…In the simulated injury prone landings, the skier got into a backward leaning position and landed asymmetrically on one ski tail with extended hips and knees (Table 1). The description of the obtained injury prone landings is consistent with other studies, where the same characteristics were observed (Bally et al 1989;Bere et al 2011;Heinrich et al 2014).…”
Section: Discussionsupporting
confidence: 90%
“…In the simulated injury prone landings, the skier got into a backward leaning position and landed asymmetrically on one ski tail with extended hips and knees (Table 1). The description of the obtained injury prone landings is consistent with other studies, where the same characteristics were observed (Bally et al 1989;Bere et al 2011;Heinrich et al 2014).…”
Section: Discussionsupporting
confidence: 90%
“…It involves the application of an active anterior drawer applied by the posterior shell of the ski boot along with powerful quadriceps contraction [1,4,5]. This repeated anterior drawer force on the proximal tibia is produced by tremendous quadriceps contraction.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of anterior cruciate ligament (ACL) injuries in Alpine skiing has increased in the past 2 decades (Bechtel, Ellman, & Jordon, 1984;Feagin et al, 1987;Hauser & Schaff, 1987;Howe & Johnson, 1982;Johnson, Ettlinger, & Shealy, 1991;McConkey, 1986). This increase has been associated at least partly with changes in the design of ski boots and the design and release settings of bindings (Bally, Boreiko, Bonjour, & Brown, 1989;Figueras et al, 1987;Johnson, Ettlinger, Campbell, & Pope, 1980;Johnson, Ettlinger, & Shealy, 1989;Johnson et al, 1991). For example, the ski boots have become higher and stiffer in the past years, thus increasing the potential for transmitting forces directly from the skis to the knee joints (Bechtel et al, 1984;Ettlinger, 1986;Hauser & Schaff, 1987;Johnson et al, 1991).…”
mentioning
confidence: 99%
“…tries to recover from this fallen-back position (Bally et al, 1989;Figueras et al, 1987). In this situation, the bindings typically do not release, and the skiers report a "snap" or "pop" in their knees, either as they are forced into a hyperflexed knee joint position or as they try to recover from the hyperflexed knee joint position by contracting the knee extensor muscles powerfully (Figueras et al, 1987).…”
mentioning
confidence: 99%
See 1 more Smart Citation